SASTRA KULINER SEBAGAI SARANA PENDIDIKAN KARAKTER (ANALISIS NOVEL GERIMIS DI ARC DE TRIOMPHE KARYA NUNIK UTAMI) - Mustapa, R. Suparman; Supratno, Haris (STKIP Subang, 2018)
Culinary literature is often associated with cooking or cooking, even though there is an implicit meaning from every literature. There is advice contained in stories about food or food. The K13 curriculum that is being applied in Indonesia is referred to as a character education based curriculum. The application of character education requires a more attractive means for students to be interested, including using culinary literature. The Drizzle Novel in the Arc De Triomphe by Nunik Utami contains stories about foods that contain moral messages. The goodness found in the Gerimis novel in the Arc De Triomphe of Nunik Utami's work is honesty, help, and responsibility wrapped in stories about culinary. The approach used in this study is a qualitative descriptive approach. The data source in this study is Drizzle in the Nunik Utami Arc De Triomphe. The process of collecting data uses the method of reading, and taking notes. After the collected data is then analyzed using content analysis. The results of the study explained that the Gerimis novel in the Arc De Triomphe of Nunik Utami's work could be used as a means of developing character education in schools.